Barium concentration, phytoavailability, and risk assessment in soil-rice systems from an active barium mining region. (July 2019) - Lu, Qinhui; Xu, Xiaohang; Liang, Longchao; Xu, Zhidong; Shang, Lihai; Guo, Jianyang; Xiao, Dean; Qiu, Guangle
Abstract: Barium (Ba) is a non-essential and toxic element. In China, intensive Ba mining and Ba salt manufacturing have led to sharp increases in Ba in the environment, but little information is available regarding Ba concentrations in paddy soil and rice. The total concentrations and phytoavailability of Ba in paddy soils and paired rice samples collected from the world's largest Ba mine in Dahebian, Tianzhu, Guizhou Province, southwestern China, were investigated. Risk assessments of Ba exposure via rice consumption were also evaluated. The results indicated that extremely high Ba concentrations existed in paddy soils, ranging between 518 mg/kg and 65, 760 mg/kg, which demonstrated severe Ba contamination, as expected. The concentrations of rice Ba varied from 0.10 to 3.5 mg/kg, and a significantly positive correlation (r = 0.51, p < 0.05) between rice Ba and water-extractable Ba was observed, suggesting that water, rather than weak acid (0.43 M CH3 COOH), chelating agents (DTPA) or neutral salts (0.1 M NaNO3, 0.01 M CaCl2 or 1 M NH4 OAc), is a suitable extractant for predicting the phytoavailable Ba in the studied soils. Risk assessments showed that residents experienced low Ba exposure via rice consumption when considered in isolation of other sources in this study area. Highlights: Elevated Ba concentrations existed in paddy soils adjacent to the Ba mine and Ba salt plant. Water-extractable Ba was a good indicator of the phytoavailability of Ba in paddy soils. Ba in rice represented low risks to human health when considered in isolation of other sources.